Differential modulation of visual object processing in dorsal and ventral stream by stimulus visibility. (October 2016) - Ludwig, Karin; Sterzer, Philipp; Kathmann, Norbert; Hesselmann, Guido
Abstract: As a functional organization principle in cortical visual information processing, the influential 'two visual systems' hypothesis proposes a division of labor between a dorsal "vision-for-action" and a ventral "vision-for-perception" stream. A core assumption of this model is that the two visual streams are differentially involved in visual awareness: ventral stream processing is closely linked to awareness while dorsal stream processing is not. In this functional magnetic resonance imaging (fMRI) study with human observers, we directly probed the stimulus-related information encoded in fMRI response patterns in both visual streams as a function of stimulus visibility. We parametrically modulated the visibility of face and tool stimuli by varying the contrasts of the masks in a continuous flash suppression (CFS) paradigm. We found that visibility – operationalized by objective and subjective measures – decreased proportionally with increasing log CFS mask contrast. Neuronally, this relationship was closely matched by ventral visual areas, showing a linear decrease of stimulus-related information with increasing mask contrast. Stimulus-related information in dorsal areas also showed a dependency on mask contrast, but the decrease rather followed a step function instead of a linear function. Together, our results suggest that both the ventral and the dorsal visual stream are linked to visual awareness, but neural activity in ventral areas more closely reflects graded differences in awareness compared to dorsal areas.